2008
DOI: 10.1211/ijpp.16.5.0008
|View full text |Cite
|
Sign up to set email alerts
|

The General Level Framework: use in primary care and community pharmacy to support professional development

Abstract: Objectives To compare practice pharmacists and community pharmacists based on the use of the General Level Framework (GLF) as a tool to support continuing professional development (CPD). Setting Primary care and community pharmacy in London and the East of England. Method The study pharmacists were self‐selected after distribution of recruitment packs in the study area through local pharmaceutical committees, primary care trusts and two large multiples. Sixty‐nine pharmacists used the framework to support thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 8 publications
1
45
0
Order By: Relevance
“…23 Documentation of pharmacist contributions is a useful tool in enhancing communication with other healthcare providers, justifying the workload, and identifying opportunities for focused drug use review. 24 Although several studies reported that most hospital pharmacists…”
Section: Discussionmentioning
confidence: 99%
“…23 Documentation of pharmacist contributions is a useful tool in enhancing communication with other healthcare providers, justifying the workload, and identifying opportunities for focused drug use review. 24 Although several studies reported that most hospital pharmacists…”
Section: Discussionmentioning
confidence: 99%
“…14 The GLF allows accurate determination of a precise described meanings and level of such competencies. 10,11,15 There is a strong connection between competency and performance. Multiple-choice tests, oral examinations, or essays can be used to test factual knowledge, but more sophisticated methods are needed to assess performance, including observation, objective structured clinical examinations, and role play using standardized or real patients.…”
Section: General Level Framework (Glf)mentioning
confidence: 99%
“…One of the most common models for the evaluation and development of pharmacists' capabilities currently in use in Europe, Asia and Australia 11,12,[15][16][17][18] is described in the General Level Framework (GLF) document. The GLF is an evidence-based framework developed by the Competency Development and Evaluation Group and in synergy with the International Pharmaceutical Federation (FIP) guiding principles for pharmaceutical education.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements of competencies have been observed in the environments which have implemented the GLF document as a training tool. 11,12,[15][16][17][18] This is the first study that reports the evidence associated with development, implementation and evaluation of pharmacists' competencies in Serbia using a validated professional development framework. The aims of this study are: 1) to show the adaptation process of the GLF document to the Serbian pharmaceutical workforce and regulations; 2) to illustrate the implementation of the Serbian-adapted GLF in a chain of the state-owned pharmacies in the Republic of Serbia, and to evaluate if there is a measurable improvement of pharmacists' competencies and monitoring of the pharmaceutical services provisions.…”
Section: Introductionmentioning
confidence: 99%